Cultivating Pancasila Learner Profiles: Exploring Bung Hatta’s Virtues of Courtesy Through Inspirational Stories in Indonesian Primary Schools - Heri Effendi; Muslim Muslim; Wirnita Wirnita; Siti Aisyah; Ashabul Khairi (Journal of Educational Sciences, 2026)
This study explores the development of Pancasila student profiles by highlighting Bung Hatta's noble values in terms of manners through inspirational stories in Indonesian elementary schools. As one of the founders of the Indonesian nation, Bung Hatta exemplifies moral values that are in line with the goals of character building embedded in the national education curriculum. This study aims to analyze how his stories can serve as effective pedagogical tools in instilling polite behaviors-an important aspect of the first and second principles of Pancasila among young learners. Qualitative descriptive methods were used to collect and analyze data from classroom observations, teacher interviews, and document reviews in several elementary schools in West Sumatra. The results indicate that integrating Bung Hatta's life story into classroom instruction significantly improved students' understanding and internalization of values related to manners such as respect, humility, and social responsibility. Teachers also reported that the use of local historical figures increased students' engagement and cultural pride. This study concludes that character education based on national role models such as Bung Hatta not only strengthens Pancasila values but also makes moral learning more relevant and impactful for elementary school students.